Single intravitreal administration of a tetravalent siRNA exhibits robust and efficient gene silencing in mouse and pig photoreceptors - Shun-Yun Cheng; Jillian Caiazzi; Annabelle Biscans; Julia F. Alterman; Dimas Echeverria; Nicholas McHugh; Matthew Hassler; Samson Jolly; Delaney Giguere; Joris Cipi; Anastasia Khvorova; Claudio Punzo (Elsevier, 2024)
Inherited retinal dystrophies caused by dominant mutations in photoreceptor (PR) cell expressed genes are a major cause of irreversible vision loss. Oligonucleotide therapy has been of interest in diseases that conventional medicine cannot target. In the early days, small interfering RNAs (siRNAs) were explored in clinical trials for retinal disorders with limited success due to a lack of stability and efficient cellular delivery. Thus, an unmet need exists to identify siRNA chemistry that targets PR cell expressed genes. Here, we evaluated 12 different fully chemically modified siRNA configurations, where the valency and conjugate structure were systematically altered. The impact on retinal distribution following intravitreal delivery was examined. We found that the increase in valency (tetravalent siRNA) supports the best PR accumulation. A single intravitreal administration induces multimonths efficacy in rodent and porcine retinas while demonstrating a good safety profile. The data suggest that this configuration can treat retinal diseases caused by PR cell expressed genes with 1-2 intravitreal injections per year.